Emperors Once More - Jepson, Duncan (New York Quercus, 2015)
Hong Kong, 2017. China has bailed out the West, but the West has defaulted on its debt. And now someone in the shadows is intent on making it pay.
Keywords: China--Hong Kong -- Conspiracies -- Police